Tempo ideal de vibração lingual sonorizada e qualidade vocal de mulheres - Zimmer, Valquíria (2011)
This study aimed to determine the optimal time of tongue vibration technique (STVT) and acoustic measures of the glottal source, spectrographic acoustic measures and technical after- subjective sensations in women without complaints and/or voice disorders and/or laryngeal. Materials and Methods: 68 young adult women were submitted to otorhinolaryngologic evaluation and speech screening to eliminate possible changes that could interfere with the results of the study. Vocal samples were collected before and after performing three sets of 15 repetitions of STVT in maximum phonation time with normal tone and habitual intensity, and 30 seconds of passive rest between each series. The acoustic analysis of voice through the Multi Dimensional Voice Program Advanced and the Real Time Spectrogram software (Kay Pentax) was used to generate broadband and narrowband spectrograms before and after the execution of STVT. The analysis of the sensations after using STVT was assessed using a questionnaire for the survey. Data were tabulated into two groups: time of maintenance of STVT up to three minutes (n=24) and time of maintenance over three minutes (n=44). Results were analyzed statistically at the significance level of 5%. Statistical analysis was performed by analysis of variance (ANOVA), Student s t test using Minitab 15.0, Pearson s coefficient of correlation and comparison tests for two proportions. Results: a significant increase of frequencies (F0) and the average frequency (MF0) was observed when STVT was performed over three minutes. A significant improvement of the long-term stability measurement (vF0), of the jitter measurements (PPQ) and of harmonic noise ratio (HNR) was observed. There was a positive correlation in all aspects of the broadband and narrowband and most of the aspects presented a very strong correlation. A predominance of positive sensations in both time intervals was observed. A very strong positive correlation between spectrographic analysis and sensations was reported after STVT in almost all aspects evaluated in broadband and narrowband. Conclusion: there were significant differences between the measurements of the glottal source after three minutes of STVT, and no significant changes occurred in the measurements with time of performance up to three minutes. There were no significant differences of the broadband and narrowband results regarding time of maintenance. Correlations between spectrographic aspects and sensations after performing STVT were positive in both time intervals of the technique. Thus, the group studied we obtained positive results in the glottal source with more than three minutes to perform the STVT, where for positive results in the vocal tract, to perform three minutes was enough.